Decoupled Lithospheric Folding, Lower Crustal Flow Channels, and the Growth of Tibetan Plateau. Issue 13 (8th July 2022) - Shin, Young Hong; Shum, C. K.; Braitenberg, Carla; Lee, Sang Mook; Lim, Mutaek; Na, Sung‐Ho; Dai, Chunli; Zhang, Chaoyang; Pan, Yuanjin; Do, Seok‐Hyeon; So, Byung‐Dal
Abstract: The growth mechanism of the Tibetan Plateau, postulated by a number of hypotheses, remains under intense debate. Our analysis of recent satellite‐based gravity model reveals that Tibetan lithosphere has been decoupled and folded. It is further evidenced by the existence of crustal melts and channel flow that have been observed by seismic and magnetotelluric explorations. Based on 3D geodynamic simulations, we elucidate the exact buckling structures in the upper crust and lithospheric mantle: at mixed wavelengths between ∼240 and ∼400 km, the lower crustal viscosity is smaller than ∼10 19 Pa·s, implicating weak lower crustal flow beneath the Plateau. This mixed wavelength is consistent with the result of our inverse gravity modeling. Our results facilitate a new plausible hypothesis that the decoupled lithospheric folding mechanism can explain the growth mechanism of the anomalously thick and wide Tibetan Plateau by conflating our idea and contemporary hypothesized scientific findings. Plain Language Summary: The Tibetan Plateau, known as the Roof of the World, is the highest and largest Plateau on Earth, whose formation involves complex and active geodynamic processes since the Late Miocene. Here we emphasize the importance of decoupled lithospheric folding and its geodynamic process that has not yet been fully considered in the contemporary hypotheses on the origin of Tibetan Plateau's formation. The deep‐seated folding structure modeled using the latest satellite gravimetry shows a structure consistent with the plate tectonic setting, which allows rocks to melt easier and flow in the lower crust underneath the Tibetan Plateau. Our hypothesis was further tested and validated by three‐dimensional numerical simulations, revealing the decoupled lithospheric folds in the collisional tectonic setting. Our study is consistent with the existence of partial melting and flow channels of the Tibetan lower crust previously discovered by geophysical explorations. Further it makes it easier to explain the morphological characteristics, magma of crustal origin, and in particular, the mass transport process in the lower crust, which is the most important factor in the formation processes of the Tibetan Plateau, than the indentation process of the strong lithosphere. Key Points: Gravity field and Steady‐State Ocean Circulation Explorer (GOCE) gravity mission detected signals of upper crust in the Tibetan Plateau, which reveals the decoupled folding of the lithosphere The decoupled folding process provides an alternative explanation of Tibetan Plateau's anomalously thick crust and flat topography Our 3D viscoelastic numerical modeling explains the wavelenths of the decoupled folding beneath the Tibetan Plateau